2005
DOI: 10.1111/j.1399-0039.2005.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and application of two novel monoclonal antibodies against 2IgB7‐H3: expression analysis of 2IgB7‐H3 on dendritic cells and tumor cells

Abstract: 2IgB7-H3 has recently been identified as a new member of the B7 family. Its expression at the protein level remains largely unknown due to the lack of the specific monoclonal antibody (mAb). To characterize the expression of 2IgB7-H3, we newly generated two mouse antihuman 2IgB7-H3 mAbs (4H7 and 21D4). We found the constitutive expression of 2IgB7-H3 on a series of tumor cell lines. Furthermore, the expression was examined on monocyte-derived dendritic cells (Mo-DCs) and DCs from CD34(+) hematopoietic progenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…9,19 Previous studies showed that B7-H3 protein can be expressed in dendritic cells, liver, lungs and prostate, 20 and most tumor cell lines. 21,22 In addition to expression on the cell membrane, B7-H3 can be released into circulation as a soluble molecule. 11 However, the physiological and pathological role of B7-H3 is far less well known.…”
Section: Discussionmentioning
confidence: 99%
“…9,19 Previous studies showed that B7-H3 protein can be expressed in dendritic cells, liver, lungs and prostate, 20 and most tumor cell lines. 21,22 In addition to expression on the cell membrane, B7-H3 can be released into circulation as a soluble molecule. 11 However, the physiological and pathological role of B7-H3 is far less well known.…”
Section: Discussionmentioning
confidence: 99%
“…Although B7-H3 mRNA is widely detected in multiple tissues in human and other species, B7-H3 protein is not constitutively expressed in these tissues [11,12]. Previous studies showed B7-H3 protein can be expressed in dendritic cells, and most tumor cell lines derived from epithelium including lung tumor cell lines A549, H1299, H460, and SPC-A-1 [13][14][15]. B7-H3 was described in early studies to costimulate the proliferation of T cells, and selectively stimulates IFN-␥ production [11].…”
Section: Introductionmentioning
confidence: 95%
“…B7-H3 is thought to serve as an accessory co-regulator of T-cell responses after initial antigen priming. At present, there is no consensus with regard to the physiological and pathological roles of B7-H3, as both immunological stimulatory and inhibitory functions have been described (Chapoval et al, 2001;Sun et al, 2002;Suh et al, 2003;Castriconi et al, 2004;Prasad et al, 2004;Steinberger et al, 2004;Wang et al, 2005;Zhang et al, 2005). It was originally identified as a co-stimulatory molecule that promotes T-cell proliferation and IFN-g production (Chapoval et al, 2001).…”
mentioning
confidence: 99%
“…B7-H3 is not expressed on quiescent lymphocytes and can be induced in activated dendritic cells, monocytes, T cells, and in some tumour cell lines (Chapoval et al, 2001;Sun et al, 2002;Steinberger et al, 2004;Zhang et al, 2005). B7-H3 is thought to serve as an accessory co-regulator of T-cell responses after initial antigen priming.…”
mentioning
confidence: 99%